THE INFLUENCE OF OCCUPATIONAL SAFETY AND MOTIVATION ON WORK PRODUCTIVITY MEDIATED BY EDUCATION AND TRAINING IN A PRIVATE PHARMACEUTICAL COMPANY, JAKARTA - Reza Adrian; PM. Budi Haryono; Fushen (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2026)
Work productivity is crucial for achieving organizational goals. Using education and training as mediating variables, this study investigates how occupational safety and work motivation influence the work productivity of employees at PT X in Jakarta. A quantitative approach was used in conjunction with a survey. After asking PT X employees to complete the survey, the Partial Least Squares–Structural Equation Modeling (PLS-SEM) method was used to analyze the data. The results showed that work motivation had a positive and significant effect on education and training, as well as work productivity. Conversely, occupational safety did not affect work productivity or education and training. Furthermore, training and education were shown to be unable to control the relationship between occupational safety and work motivation on work productivity. Compared with perceptions of occupational safety and existing education and training programs, these findings indicate that motivation has a greater influence on increasing work productivity at PT X. Therefore, the company should evaluate its education and training programs and strengthen strategies to improve work motivation to meet operational needs and improve work productivity.